Did Louis X of France mint deniers tournois? (Notes on a few deniers tournois à la croisette) - Bontas, Andrei (KOINON: The International Journal of Classical Numismatic Studies, 2019)
After the death of Philippe IV starts a period of about 15 years during which the small billon currencies of the reign, the tournois and the parisis, both deniers and oboles, seem to be fading from the royal mints. There are no definite parisii or tournois attributed with certainty to the reigns of Louis X, Philippe V or Charles IV. There are some hints to possible issues during this period, for instance Duplessy 235 and 237, some presumed ‘petits’ of Philippe V, the minting of which was ended by Charles IV in 1322 or the attempt to assign the tournois à la croisette to the reign of Louis X, in the light of the Ordonnance de Lagny-sur-Marne of 1315, ‘vers les fetes de Noel.’